Diseño de un prototipo geotérmico con intercambiador de calor tierra-aire para la climatización de viviendas con condiciones ambientales de temperatura mayores a 30 °C (2022)
A part of the environmental pollution of the planet can be attributed to construction activities, therefore, it is necessary to implement measures that promote the use of energy efficiency systems; Therefore, the Bruntland report published for the United Nations in 1987, the declarations stipulated in Rio de Janeiro on the year 1992 and the so-called Kyoto Protocol, promote the commitment for states to act in the face of the global energy crisis and to implement renewable energies. renewable, this research is developed to provide an alternative energy solution to conventional air conditioning systems. This project aims to analyze the operation of a geothermal air conditioning system by ground-air heat exchanger (GAHE), which was divided into a phase of theoretical study and practical study, 65 environmental, thermal and dimensional variables were collected, which are mathematically analyzed by calculations with the help of the De Paepe & Janssens thermal analysis model. The results obtained were: 20.4 °C of outlet temperature, 248 W of total heat transferred, a pressure drop of 165.68 Pa and an efficiency of 72% of the GAHE.